System identification and modeling of UP ICE L1 & L2 building - De Guzman, Carl Louis S.
Monitoring the condition of structures is important in early detection of damages and renovation to prevent it from failing. Several methods in structural health monitoring make use of modal parameters such as natural frequency, damping ratio, and mode shapes in determining, locating, and quantifying damages on the structure. This study aims to determine the modal properties of the columns of the Structural (L1) and Construction (L2) Engineering laboratories building in the ICE complex. Building vibration were recorded by conducting free vibration test on columns. Modal analysis of these recorded vibrations was done by using two methods, one is Peak-Picking Method which is a frequency-domain technique, and the other is Stochastic Subspace Identification Technique which is a time-domain technique. To compare the modal frequency obtained from the experiment, the theoretical values of the modal frequency were obtained by making a simulation model of the structure using SAP2000, a structural software for analysis and design. Frequencies obtained from the experiment ranges from 129 to 241 Hertz. The two methods used in the analysis produced similar and accurate results. On the other hand, the simulation model produced frequencies from 127 to 221 Hz. Comparing the model and the actual data, columns at the corners of the structure and along one side of the structure has a large difference on the frequencies obtained. Damping ratio of the columns from the experiment were computed using Logarithmic Decrement. The calculation produced damping ratio values of 0.0317 to 0.0761. The use of mounting tape to attach the accelerometers has an effect of the damping observed which makes it higher than the usual damping ratio of 0.02 to 0.05.